2018
DOI: 10.1002/jcp.26376
|View full text |Cite
|
Sign up to set email alerts
|

XIST/miR‐544 axis induces neuropathic pain by activating STAT3 in a rat model

Abstract: An increasing number of studies have reported that lncRNAs are responsible for the development of neuropathic pain. In our current study, chronic constriction injury (CCI) rat models were established and we observed that lncRNA XIST was greatly increased. Knockdown of XIST can relieve pain characteristics including both mechanical and thermal hyperalgesia in CCI rats. Meanwhile, XIST down-regulation could inhibit neuro-inflammation by reducing expression of inflammatory cytokines including tumor necrosis facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 33 publications
2
54
1
Order By: Relevance
“…Sun et al showed that XIST inhibition could reduce inflammatory pain through inhibiting Nav1.7 by acting as a sponge for miR‐146a, suggesting a promising strategy for fighting inflammatory pain . Moreover, XIST knockdown inhibited neuroinflammation by suppressing TNF‐α, COX‐2, and IL‐6 expression in CCI rats . However, there are few literature studies on the function and mechanism of XIST in pneumonia.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Sun et al showed that XIST inhibition could reduce inflammatory pain through inhibiting Nav1.7 by acting as a sponge for miR‐146a, suggesting a promising strategy for fighting inflammatory pain . Moreover, XIST knockdown inhibited neuroinflammation by suppressing TNF‐α, COX‐2, and IL‐6 expression in CCI rats . However, there are few literature studies on the function and mechanism of XIST in pneumonia.…”
Section: Discussionmentioning
confidence: 60%
“…XIST was reported to promote cancer development and could cause inflammation response in chronic constriction injury, neuropathic pain, and chronic pain . To profile the expression of XIST in LPS‐injured WI‐38 cells, qRT‐RCR analysis was evaluated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For miR-32-5p and Notch-1 interaction, the putative and mutated miR-32-5p target binding sequences in Notch-1 were synthesized and cells were co-transfected with the WT or MUT Notch-1 reporter gene plasmid or pmirGlo plasmids using Lipofectamine ® 2000 (Invitrogen). At 48 h post-transfection, cells were harvested and the firefly luciferase activity was measured using a dual-luciferase reporter assay system (Promega) and normalized to Renilla luciferase activity ( Jin et al, 2018 ; Hu et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…1b). In recent studies, XIST appeared to function as miRNA sponge sequestering miR-137, miR-150, miR-544, and miR-154-5p, then regulating the expression of relevant binding proteins or the release of inflammatory cytokines that accelerated NP progression [36][37][38][39][40]. In addition, Gu et al [41] demonstrated that XIST effectively becomes a miRNA sponge for miR-494, also acting as a competitive endogenous RNA (ceRNA), and contributed to neuronal apoptosis through the downregulation of AKT phosphorylation in the SCI model.…”
Section: Kcna2 Antisense Rna: Cis-acting Repressormentioning
confidence: 99%